New coumarin-based mannich bases: synthesis and in vitro cytotoxic evaluation - Tran, Duy Thanh; Vu, Xuan Thach; Ho, Duc Cuong; Dao, Phuong Lan; Vu, Tran Khac (Vietnam Journal of Science and Technology, 2025)
This paper presents the synthesis of novel Mannich bases 4a-h derived from coumarin in good yields through a three-step procedure. Initially, the Knoevenagel reaction of 2,4-dihydroxybenzaldehyde (1) with Medrum’s acid in water under reflux for 10 hours afforded coumarin acid (2) in 95 % yield. Compound 2 was next reacted with 3-methoxybenzylamine and 4-methoxybenzylamine in DMF using EDC and DMAP as a coupling system for 10-12 hours to give compound 3a-b in 76-83% yield. Finally, the reaction of 3a-b with the excess of paraformadehyde and secondary amines in ethanol under reflux for 20 hours gave new coumarin-based Mannich bases 4a-h with yields ranging from 30% to 69%. The structures of the Mannich bases were characterized using NMR and MS spectra. Bioassay results revealed that some of the synthesized Mannich bases exhibit cytotoxic activity against SKLu-1 and MCF-7 cell lines, ranging from weak to moderate effect.